ANALYSIS OF THE EARLY-TIME OPTICAL SPECTRA OF SN 2011fe IN M101 - Parrent, J; Howell, D; Friesen, B; Thomas, R; Fesen, R; Milisavljevic, D; Bianco, F; Dilday, B; Nugent, P; Baron, E; Arcavi, I; Ben-Ami, S; et al. (2012)
The nearby Type Ia supernova (SNIa) SN2011fe in M101 (cz = 241kms -1) provides a unique opportunity to study the early evolution of a "normal" SNIa, its compositional structure, and its elusive progenitor system. We present 18 high signal-to-noise spectra of SN2011fe during its first month beginning 1.2days post-explosion and with an average cadence of 1.8days. This gives a clear picture of how various line-forming species are distributed within the outer layers of the ejecta, including that of unburned material (C+O). We follow the evolution of C II absorption features until they diminish near maximum light, showing overlapping regions of burned and unburned material between ejection velocities of 10,000 and 16,000kms-1. This supports the notion that incomplete burning, in addition to progenitor scenarios, is a relevant source of spectroscopic diversity among SNeIa. The observed evolution of the highly Doppler-shifted O I λ7774 absorption features detected within 5days post-explosion indicates the presence of O I with expansion velocities from 11,500 to 21,000kms-1. The fact that some O I is present above C II suggests that SN2011fe may have had an appreciable amount of unburned oxygen within the outer layers of the ejecta. © 2012. The American Astronomical Society. All rights reserved..